Metal- and light-free direct C-3 ketoalkylation of quinoxalin-2(1H)-ones with cyclopropanols in aqueous medium - More, Devidas A.; Mujahid, M.; Muthukrishnan, M. (ChemistrySelect, 2022)
Direct oxidative C-3 ketoalkylation of quinoxalin-2(1H)-ones with cyclopropanols using ammonium persulfate in an aqueous medium has been achieved in a moderate to good yield. The reaction does not require metals, light-source, or catalysts to facilitate the reaction and could be efficiently utilized to construct a wide range of biologically relevant 3-ketoalkylated quinoxalin-2(1H)-ones.
Keywords: aqueous medium; cyclopropanols; ketoalkylation; metal-free; quinoxalin-2(1H)-ones